2018
DOI: 10.3390/electronics7070107
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Application of Electrical Resistivity Tomography for Investigating Seawater Intrusion

Abstract: Seawater intrusion is a major issue in coastal areas, and the traditional technology of investigation mainly makes use of drilling for water level observation and sample analysis of groundwater; as drilling data is an information of points, it will cost more if it is extended to be information on the surface. Non-destructive geophysical exploration technology has been used in the investigation of the underground environments at all kinds of contaminated sites in recent years. Seawater intrusion is also a groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…Such high contrasts make TL-ERT a suitable tool (i) to monitor seawater intrusion which could lead to groundwater salinization (Chen et al. 2018 ; Palacios et al. 2020 ) and (ii) to characterize submarine groundwater discharge when contaminants flow from land to sea (Henderson et al.…”
Section: Review Of Tl-ert Applications Over the Past 30 Yearsmentioning
confidence: 99%
“…Such high contrasts make TL-ERT a suitable tool (i) to monitor seawater intrusion which could lead to groundwater salinization (Chen et al. 2018 ; Palacios et al. 2020 ) and (ii) to characterize submarine groundwater discharge when contaminants flow from land to sea (Henderson et al.…”
Section: Review Of Tl-ert Applications Over the Past 30 Yearsmentioning
confidence: 99%
“…https://dx.doi.org/10.22161/ijeab.73. 4 26 means of time-lapse observed a delay effect existing between seawater intrusion and tidal action.…”
Section: Introductionmentioning
confidence: 98%
“…The gap of electrical resistivity using geophysical techniques between seawater (0.2Ωm) and freshwater (> 5Ωm) is able to map the subsurface groundwater salinity distribution (Werner et al, 2013). The research by (Chen et al, 2018) showed that Electric Resistivity Tomography could detect the front edge of the seawater intrusion and ISSN: 2456-1878 (Int. J. Environ.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, 2D ERT exploration has been extensively used in geotechnical engineering and environment engineering investigations and monitoring, such as geologic surveys [8][9][10], fault surveys [11][12][13][14][15][16][17], slipping plane surveys and monitoring [18][19][20][21][22][23], groundwater investigations and pollution monitoring [24,25], seawater intrusion investigations [26][27][28][29], dam leakage investigations and monitoring [30][31][32][33], landfill leakage investigations and monitoring [34][35][36][37][38], and archaeological surveys [39,40]. The 3D DC resistance method has been used by scholars [41][42][43], but it is difficult to be implemented, and the site is often limited to the measurement space, so the 2D DC resistance method is still the main method in engineering.…”
Section: Introductionmentioning
confidence: 99%